Diversity and Community Structure of Dragonflies (Odonata) in Various Types of Habitat at Lakarsantri District, Surabaya, Indonesia - Muhamad Azmi Dwi Susanto; Nirmala Fitria Firdhausi; Saiful Bahri (Universitas Gadjah Mada, 2023)
Dragonflies are insects that are very dependent on the existence of freshwater ecosystems, However, the population of dragonflies in urban freshwater ecosystems is at risk due to a number of issues. Consequently, it is essential to carry out research and efforts to preserve dragonflies in urban areas. This study aims to provide information about the diversity and structure of dragonfly communities in various habitat types in the Lakarsantri, Surabaya. Data collection in this study was carried out in the habitat types of ponds, reservoir, river, and rice field in July to September 2021. The study results show there are 22 species from 4 families with a total of 827 individuals. Analysis of the Shannon-Wiener diversity index showed that the highest value of dragonfly diversity was found in a pond, with a value of H' = 2.40, and the location with the lowest value was a river, with a value of H' = 1.77. At four research locations that have different aquatic ecosystems, the community structure of dragonfly is also different. The composition of the dragonfly community structure at the reservoir location has similarities to a pond, and at a river location, it has similarities to a paddy field. Differences in abiotic factors consisting of light intensity, humidity, and temperature at each study location have a correlation with differences in dragonfly community structure. In addition, the composition of the vegetation at each location is also one of the factors causing differences in the structure of the dragonfly community.